Multi-employer bargaining : industrial relations system in the banking industry in Nigeria - Etukudo, Akanimo J. (Ilfracombe : Stockwell, 1971)
Contents: Clerical Workers and Trade Unions; The Bank Employees' Unions; The Nigerian Bankers (Employers) Association; The Case for Industry-Wide Bargaining; The Actual Bargaining; Implementing the Agreement; Compulsory Arbitration; Conclusion
Includes bibliographical references.
rpm 15/03/2018
Loans
Keywords: Collective bargaining